exercițiu 12.........

Explicație pas cu pas:
[tex]2 \sqrt{3} ( \sqrt{6} - \sqrt{5} ) - 2 \sqrt{18} + 2 \sqrt{15} = 2 \sqrt{18} - 2 \sqrt{15} - 2 \sqrt{18} + 2 \sqrt{15} = 0[/tex]
[tex]5 \sqrt{2} ( \sqrt{2} - \sqrt{6} ) - \sqrt{16 - 3 \times 2} + 10 \sqrt{3} = 5 \times 2 - 5 \times 2\sqrt{3} - \sqrt{10} + 10 \sqrt{3} = 10 - 10 \sqrt{3} - \sqrt{10} + 10 \sqrt{3} = 10 - \sqrt{10} [/tex]
[tex]2 \sqrt{12} - 2 \sqrt{2} (\sqrt{30} \div \sqrt{5} - \sqrt{5}) - \sqrt{40} = 2\sqrt{12} - 2 \sqrt{2} (\sqrt{6} - \sqrt{5}) - \sqrt{4 \times 10} = 2 \sqrt{12} - 2 \sqrt{12} + 2 \sqrt{10} - 2 \sqrt{10} = 0 [/tex]